Meningkatkan Literasi Informasi Mahasiswa Universitas Terbuka Melalui Teknologi Artificial Intelligence - Pandu Ristiyono, Mohamad (Perpustakaan Universitas Gadjah Mada, 2025)
This study aims to investigate and enhance the utilization of artificial intelligence in the libraries of Open University to boost students' information literacy. In the digital age, artificial intelligence applications hold the promise of improving both the accessibility and quality of library services, along with facilitating personalized user experiences through recommendation systems, chatbots, and automated data processing. Nonetheless, the implementation of artificial intelligence also introduces ethical issues, including data privacy and algorithmic bias. The research employed a qualitative approach with case study analysis to pinpoint best practices in artificial intelligence deployment and its ethical ramifications. Findings indicated that out of 450 respondents, 45% were able to download information, 22% were unable to do so, and 33% were uncertain. The integration of artificial intelligence can enhance operational efficiency and user experience, as long as it is complemented by policies that uphold integrity and fairness. This study advocates for the creation of ethical guidelines and staff training, with the aspiration that Open University can lead in the responsible use of artificial intelligence technology in the realm of distance education. Artificial Intelligence; AI ; Information Literacy ; Library Distance Education ; Universitas Terbuka ; Ethical Services